Faith-Based Organizations as Learning Intermediaries in Pandemic Governance - Endang Tirtana; Azhari Aziz Samudra; Ma'mun Murod (Journal La Edusci, 2025)
This study examined the role of learning-oriented educational governance in crisis response through a qualitative case study of the Muhammadiyah Disaster Management Centre (MDMC) during the COVID-19 pandemic in Indonesia. Drawing on community participation theory, collaborative governance, and public sector innovation frameworks, the study explored how participation, collaboration, and innovation functioned as interconnected educational processes. Data were collected through semi-structured interviews, document analysis, and non-participant observation, and analyzed using thematic analysis. The findings indicate that MDMC’s crisis response extended beyond humanitarian action and operated as an educational governance mechanism that strengthened community learning, institutional coordination, and adaptive innovation. Participatory educational engagement enhanced public health literacy and social trust, while collaborative governance facilitated inter-organizational learning across sectors. Innovation emerged as a learning-driven process that institutionalised knowledge into sustainable crisis-response practices. This study proposes an integrative participation model that highlights education as a central mechanism in managing complex societal crises. The findings contribute to educational governance literature by demonstrating the capacity of faith-based organisations to act as learning intermediaries that enhance community resilience and policy legitimacy during emergencies